AGROCHEMICAL PROPERTIES OF VIRGIN LIGHT SERIOZEMS OF THE GUZOR RANGE (Scientific journal of the Fergana State University, 2025)
In this article we will consider the agrochemical properties of coarse-grained loose soils depending on their natural origin. In addition, depending on the climatic conditions in which the soil is located, Agrochemical properties of soil from the lower layers of subsoil 1; 2; 3 and 4 of the lower layers of the lower soil layer constitute a humus content of 0.163-0.326%, total nitrogen 0.014-0.028%, vegetation cover affects the agrochemical properties of its surface layers for some time, total phosphorus 0.021-0.038%, total potassium 1.327-1.687%, residual phosphorus (P2O5) 2.3-3.5 mg/kg, variable potassium (K2O) 90.7-158.2 mg/kg, pH value was 7.63-7.68.